380 A Rapid CSF Assay Accelerates Diagnosis and Treatment Initiation for CNS Neoplasms. (April 2023) - Gupta, Mihir; Bradley, Joseph; Massaad, Elie; Burns, Evan; Forst, Deborah; Cahill, Daniel P.; Barker, Frederick George; Jordan, Justin; Dietrich, Jorg; Lennerz, Jochen K.; Nahed, Brian V.; Carter, Bob S.; et al.
Abstract : INTRODUCTION: The low yields of CSF studies and serologies in current diagnostic workflows for suspected CNS neoplasms often lead to neurosurgical biopsies of high-risk lesions. To address this need, we developed an assay to rapidly identify hallmark mutations of CNS neoplasms in CSF. METHODS: Targeted Rapid Sequencing (TetRS) was developed as a qPCR-based method to detect IDH1/2, TERT promoter, BRAF, H3F3A, and MYD88 mutations in CSF-derived DNA within 80 minutes of collection. CSF was prospectively collected over 18 months from 98 patients with suspected new CNS neoplasms. Results were utilized in clinical decision-making. RESULTS: 40 of 98 patients were ultimately diagnosed with a neoplasm. TetRS detected a mutation in 15 out of 40 patients with a neoplasm (37.5%), including cases of CNS lymphoma, glioblastoma, IDH-mutant brainstem glioma and H3K27M-mutant diffuse midline glioma. Detection of a mutation accelerated diagnosis in comparison to cases where a mutation was not detected (median 0.5 vs 10.5 days, p < 0.00001). In multiple cases, a positive TetRS result obviated the need for biopsy and enabled initiation of disease-directed therapy. In one such case, detection of the MYD88 L265P variant was diagnostic of CNS lymphoma, enabling methotrexate and rituximab initiation within 3 days of admission. Results of repeated CSF samplings correlated with treatment response and recurrence. In another case, detection of the IDH1 R132G variant was diagnostic of IDH-mutant brainstem glioma, enabling IDH inhibitor and radiation therapy, with clinical and radiographic response. CONCLUSIONS: The targeted cell-free DNA panel for CSF presented here is a novel tool to rapidly, cost-effectively and broadly diagnose CNS neoplasia, initiate therapies and follow disease progression in the absence of neurosurgical tissue sampling.